Development of novel in vitro and in vivo models for determining primary events in HLRCC tumourigenesis - O'Flaherty, L; Linda O'Flaherty (2012)
Germline mutations of fumarate hydratase (FH), encoding an enzyme of the tricarboxylic acid (TCA) cycle, predispose affected individuals to hereditary leiomyomatosis and renal cell cancer (HLRCC). FH-deficient cells and tissues have been shown to accumulate fumarate, exhibit S-(2-succinyl) cysteine (2SC) protein modifications and to constitutively express hypoxia-inducible factor alpha (HIF-1α and -2α), under normoxic conditions. This thesis presents a phenotypic characterisation of Fh1-/- mouse embryonic fibroblasts (MEFs), generated from previously reported conditional Fh1 knockout mice, as a new in vitro system for investigating and identifying biochemical and metabolic pathways that are dysregulated as a result of Fh1 inactivation. These cell lines reproduced the aforementioned phenotypes, in addition to an observed shift from oxidative phosphorylation (OXPHOS) to glycolytic metabolism. Re-expression of either full length, mitochondrial-targeted FH (Fh1-/- +FH) or cytoplasmic FH (Fh1-/- +FHΔMTS) in Fh1-deficient MEFs was sufficient to reduce intracellular fumarate and to correct for the dysregulation of the Hif pathway. These results were of particular interest as they demonstrated that normoxic stabilisation of Hif-1α occurs independently of the persistent mitochondrial defect observed in Fh1-/- +FHΔMTS MEFs. These findings were corroborated in vivo following the development of transgenic mouse models, ubiquitously expressing either FH or FHΔMTS in mice with targeted inactivation of Fh1 in renal tubular cells. Surprisingly, the cytoplasmic-restricted FH (FHΔMTS) transgene was just as efficient as the transgenic mice expressing mitochondrial-targeted FH at rescuing the cystic phenotype associated with Fh1-deficiency in the kidneys. As the function of cytoplasmic FH has remained poorly understood, these results go some way to extricating a role for this isoform of FH. The results of this thesis demonstrate that these novel in vitro and in vivo models, used either alone or in combination, are a versatile and robust paradigm for studying altered cell metabolism in not only HLRCC but other diseases associated with metabolic dysregulation.